The prospects of happiness in the digital age: the brazilian case (Research, Society and Development, 2021)
The main objective of this article is to investigate the impact of new information and communication technologies on human and social relations, with regard to the feeling of happiness and subjective well-being. In other words, we try to demonstrate, as a working hypothesis, that there is a close relationship between the new social mediations and the establishment of a more autonomous culture and, therefore, of well-being, which is in the genesis of the Network Society in this Digital Age. Social networks are a digital platform that enables and enhances mass self-communication, sociability, whose practice tends to establish a culture linked to autonomy and empowerment, creating the process of individuation. The data analyzed in our research show that people who are more connected to the network tend to be happier, nurturing a feeling of greater freedom and autonomy. The empirical basis of this article is the seventh wave of the World Values Survey (WVS, 2017-2020), a quantitative survey type survey, which we will use to demonstrate our argument.